Power-Frequency Electromagnetic Fields In The Home - Farag, A.S. (2020)
Attention has recently focused on the low frequency electromagnetic fields in homes. Public are interested in knowing the domestic EMF fields to help determine whether exposure to these fields causes ill health and, in particular, to provide measure of the EMF environment for an epidemiological survey. Information on the sources of home electromagnetic fields and their characteristics will be needed in order to assess longterm or past exposure to such fields and to evaluate effective methods for modifying the levels of fields should that become necessary. Residential measurement consist of a series of spot readings recorded inside frequently occupied rooms. Each spot measurement consists of a single maximum magnetic flux reading recorded by a direct reading instrument at a fixed location and time. Magnetic field recordings in different locations and current readings in different conductors associated with each residence over a one day time period is successfully done. Residential magnetic field sources are identified: nearby transmission and distribution lines, residential grounding system currents, and unusual wiring configurations. Appliance, as magnetic field sources, were also measured. The purpose of this paper is to put into perspective the dominant magnetic fields to which people are exposed at home. The extensive data presented are useful for understanding variations of field levels that can be encountered in various places and for estimating possible residential exposure levels.